Responding Proteins for HaCaT cells against 2,4-dinitrobenzene sulfonic acid stimulation-a proteomic study - Ming-Zhong Sun; Chunmei Guo; Yuling Yin; Jintao Lin; Shuqing Liu (Journal of Animal and Plant Sciences, 2016)
2,4-dinitrobenzene sulfonic acid (DNBS) contributes to the incidences of allergic dermatitis, inflammatory enteritis and colon cancer. In this study, the responding proteins of human keratinocyte HaCaT cells against DNBS stimulation were separated by two-dimensional difference in gel electrophoresis(2DDIGE), quantified by DeCyder software, post-stained by Deep Purple. And the tryptic digested proteins were identified by high performance liquid chromatography combined to nano-electro-spray ionization tandem mass spectrometry (HPLC-nESI-MS/MS) or matrix-assisted laser adsorption ionization (MALDI) MS. Six most up-regulated proteins in HaCaT against DNBS stimulation were chromosome X ORF 26 (Cxorf26), co-chaperone P23 (PTGES3), calmodulin (CALM3), interferon-gamma inducing factor precursor (IL-18), smooth muscle/non-muscle myosin alkali light chain (MYL6)and breakpoint cluster region protein 1 (BANF1). Two most down-regulated proteins were elongin B isoform alpha (TCEB2) and ribosomal protein L23 (RPL23). Their level changes were further validated by Western blotting and qRT-PCR assays. DNBS affects HaCaT proteome. Most of identified protein candidates were reported for the first time to be involved in skin cell damage to chemical stimulation. This work contributes to the understandings of risk assessment and toxicological mechanism of skin diseases caused by chemical carcinogens.
Keywords: DNBS; HaCaT; DIGE; proteomics